The Content of Non Verbal Communication Values in the Book Sulam Al-Munawwaraq Fil ‘Ilmi Mantiq - Halimatussa’diah Halimatussa’diah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Non-verbal communication is often used to describe feelings, emotions, and others. Non-verbal communication can strengthen and complement verbal communication. Therefore, in life must combine the two communications. Like the nazham contained in the al-Munawwaraq embroidery Fil ‘Ilmi Mantiq. Which explains about lafadh and ghairu lafadh both are related to one another. So that both the majority of students and some teachers who study the book  sulam al-Munawwaraq Fil ‘Ilmi Mantiq  do not know that there is a discussion of communication in the nazham. The phenomenon finally motivated a study entitled "Analysis of Non Verbal Communication Content in the book al-Munawwaraq Fil‘ Ilmi Mantiq". This study is focused only on a nazham found in the book sulam al-Munawwaraq Fil ‘Ilmi Mantiq, the nazham is conducted using the library research method, namely research carried out using literary literature, such as the yellow books, notes, and previous research report. This study yielded several answers, namely non-verbal communication in the book Sulam Al-Munawwaraq is found in the nazham was violated, as well as the value of non-verbal communication in the book sulam al-Munawwaraq Fil ‘Ilmi Mantiq  namely in the discussion of ghairu lafdhiyyah. The same is true of non-verbal communication put forward by communication experts. Then it can be concluded that the non-verbal communication contained in the book sulam al-Munawwaraq Fil ‘Ilmi Mantiq is exactly the same as the non-verbal communication stated by communication experts.